Case Study : Noursyaa Fragrance and Cosmetics (LAWAraa Cosmetics) / Anis Azmi - Azmi, Anis (2021)
Cosmetics is a substance intended to be applied to the human body for cleansing, beautifying, promoting attractiveness, or altering the appearance without affecting the body's structure or functions. Included in this definition are skin creams, lotions, perfumes, lipsticks, fingernail polishes, eye and facial makeup preparations, permanent waves, hair colours, toothpastes, and deodorants, as well as any material intended for use as a component of a cosmetic product. The founder of this company is led by Puan Nor Natasha Binti Muhammad who is also assisted by her husband, En Mohd Azmanizam Bin Jusoh as the Founder's assistant. The company has 2 managers who assist in the management of the company to ensure the company is in good condition, orderly and systematic. They are Wan Nur Shaherah Binti Wan Razali and En Muhammad Noor Sabri Bin Samso Anuar. Mohammad Izzat Shafiq Bin Maznee is the person who manages the company's marketing. He will provide materials to promote the product to the community through social media sites. The company also has 3 admins who will each assist in taking orders from agents and customers. The company has released the first edition lipmatte themed fruity edition. This first edition comes with 5 colour options to suit all skin types in Malaysia. This lipmatte provides benefits to the wearer because it can provide maximum health to the lips. According to the founder, she will be releasing a baby -sized lipmatte with a Raya edition theme.